Representasi Perempuan Modern dalam Novel Azzamine Karya Sophie Aulia pada Karakter Jasmine: Kajian Psikoanalisis Sigmund Freud - Auleyah Tri Ulfah; Agus Syaripudin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This research analyzes the representation of the modern woman in Sophie Aulia's novel Azzamine, focusing on the main character, Jasmine, using Sigmund Freud's psychoanalytic theory. The study aims to deeply analyze Jasmine's personality structure (id, ego, superego) and emotional classification, and to identify and explain her internal conflicts that reflect the reality of modern women. This research employs a descriptive qualitative method , with data sourced from dialogues and character quotes in the novel that are relevant to the psychoanalytic study. The findings reveal Jasmine as a complex, independent, and spirited modern woman who experiences a profound internal struggle between her desire for personal freedom and autonomy (id) and the constraints of religious and traditional expectations (superego), with the ego serving as the mediator to find balance. These internal conflicts reflect the broader dilemma faced by modern Muslim adolescents in negotiating their individual identity while adhering to social and religious values. The research contributes a new perspective on gender dynamics in contemporary Indonesian popular literature.